A New Benzofuran Derivatives from Flue-Cured Tobacco and Its Anti-Tobacco Mosaic Virus Activity - Liu, Chunbo; Shen, Qinpeng; Zhang, Fengmei; Zhang, Tao; He, Pei; Zhu, Ruizhi; Wang, Kunmiao; Liu, Zhihua; Yang, Guangyu; Chen, Zhangyu (Asian Journal of Chemistry, 2015)
A new benzofuran derivative, (2S,3R,4R)-3,4-dihydroxy-2,7-dimethoxy-3,4-dihydro-1(2H)- dibenzofuranone (1), was isolated from the leaves of flue-cured tobacco (a variety of Nicotiana tabacum L). Its structure was elucidated by spectroscopic methods, including extensive 1D and 2D NMR techniques. Compound 1 was also tested for its anti-tobacco mosaic virus activity and it shows potential anti-tobacco mosaic virus activity with inhibition rates of 42.3 %.